Differential Applicability of Criminological Theories to Individuals? The Case of Social Learning vis-à-vis Social Control. (April 2018) - Ward, Jeffrey T.; McConaghy, Megan; Bennett, Juwan Z.
The current study uses finite mixture models (FMMs) to examine whether competing theories—social learning and social control—are differentially applicable to individuals. Posterior probabilities reveal that 85% of individuals are most consistent with social learning theory ("learners"), whereas 15% are most consistent with social bonding theory ("bonders"). Relative to bonders, learners have significantly lower alcohol consumption and alcohol use risk—as denoted by learning and bonding variables. Results reveal generally stronger variable effects in the FMM as compared with the full-sample ordinary-least-squares (OLS) regression, particularly for differential association and belief. OLS regressions among classified subsamples resulted in substantial gains in explained variance among learners but no improvements among bonders. Implications of differential applicability of theories for assessments of theoretical validity and policy development are discussed.